Síntese assistida por micro-ondas e caracterização de óxidos de manganês para aplicação em dispositivos de armazenamento de energia - Silva, João Pedro da (2015)
The oxides Mn3O4, LiMn2O4and their doped derivatives, LiMnij98Gaojo2O3j98Sojo2, LiMni,9oGao,ioO3,9oSo,io, LiMni,98Alo,o2O3,98So,o2 and LiMni,9oAlo,ioO3,9oSo,io were produced by means of an alternative route: the microwave-assisted solid-state synthesis. Mn3O4 was produced from an electrolytically obtained s-MnO2, by using microwave heating for 5 min. For LiMn2O4 and doped derivatives, solid mixtures of LiOH.H2O and s-MnO2, or LiOH.H2O and Mn3O4 were microwave heated for varying times (3 to 5 min). The synthesis precursors and the final products were characterized by means of X-rays diffractometry (XDR), thermogravimetry (TG), diferential thermogravimetric analysis (DTA), Fourier transform infrared (FTIR) and Raman spectroscopies, and scanning electron microscopy (SEM). XRD results indicated that, for LiMn2O4 and doped derivatives, the best synthesis conditions were achieved when using Mn3O4 as the precursor, i5o mg of reaction mixture, and synthesis time of 2.5 min. Quantified by XRD analyses, the materials presented secondary phases resulting in 8i - 93% mass percentage of the LiMn2O4 phase for the doped materials, and 92% for the non-doped material. For comparison, a commercial material was analyzed, resulting in 93% for the LiMn2O4 phase. Electrochemical characterizations were performed for the produced Mn3O4 e LiMn2O4 by means of cyclic voltammetry and galvanostatic charge-discharge tests, employing electrodes constituted by 85% oxide / io% acetylene black / 5% PVDF. Tested as supercapacitor, the Mn3O4, having average size particles of 35o nm, furnished specific capacitance of 2o6 F g4 and considerable electrochemical stability with charge retention of -60% after 5ooo cycles of charge and discharge. Tested as lithium-ion battery cathodes, all the lithium manganese oxides presented charge-discharge profiles characteristic of the LiMn2O4, furnishing specific capacity values in the range 87 - 108 mA h g-1. Contrary to the expectations, the material presenting the best electrochemical stability was the non-doped LiMn2O4, with charge retention of 76% after 200 cycles of charge and discharge.